FAKTOR PENENTU KINERJA MANAJERIAL SKPD DI KOTA BENGKULU - Melinda, Rekha; Fadli, Fadli (UNIB Press, 2016)
This study aims to examine the effect of public accountability, clarity of budget targets, and management control systems on SKPD managerial performance.The population of this study was all SKPDs of Bengkulu City. Data collection using a questionnaire. Obtained as many as 89 respondents consisting of echelon II, echelon III, echelon IV officials. Data analysis using multiple linear regression.The results showed that public accountability, clarity of budget targets, and management control systems had a positive and significant effect on SKPD managerial performance.